The Study of Music in Anthropology - Marija Ristivojević (University of Belgrade, 2016)
Contemporary anthropology is characterized by a wide array of research topics, with music becoming an increasingly important field of study, which still remains unexplored, at least as far as the interrelationship of music and culture is concerned. However, it should be emphasized that music has been studied within the discipline in different ways. In that sense, the aim of this paper is to point out some of these differences, through taking the dominant theoretical postulates into account. The relevance of the concept of music for anthropological study is evident in the fact that it is a socio-cultural phenomenon which functions as both a cultural artifact and an active element through which different levels of cultural identification are shaped (the individual, collective, local, ethnic), which itself points to the fact that anthropologists themselves don’t necessarily need to engage with “traditional” music. Essentially, any type of music which means something to a group of people is fair game, as evidenced by the growing interest in the phenomenon of popular music in domestic as well as foreign scientific circles.